1991
DOI: 10.1007/bf00405001
|View full text |Cite
|
Sign up to set email alerts
|

Binding and biological effects of insulin, insulin analogues and insulin-like growth factors in rat aortic smooth muscle cells. Comparison of maximal growth promoting activities

Abstract: Binding and growth promoting effects of insulin, insulin analogues modified in the B chain, proinsulin, insulin-like growth factor-I and -II were studied in cultured rat aortic smooth muscle cells. Specific binding of 125I-insulin was 0.9 +/- 0.2% of total 125I-insulin added, and the IC50-value was estimated to 8.9 pmol/l. The insulin analogue B10 Asp tended to be more potent than insulin in displacing 125I-insulin, B28 Asp was equipotent, B9 Asp/B27 Glu was approximately 100 times less potent and insulin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 27 publications
6
63
2
Order By: Relevance
“…The binding of insulin X10 to hybrid receptors is unknown at present, but is currently under investigation. Some studies have found an increase in the maximal attainable response after stimulation with insulin X10 [18,21], whereas this has not been found by others [11,19,38]. However, it remains a possibility that in some cell types and for some responses, insulin X10 may be able to induce a higher response than human insulin.…”
Section: Understanding Insulin X10mentioning
confidence: 67%
See 1 more Smart Citation
“…The binding of insulin X10 to hybrid receptors is unknown at present, but is currently under investigation. Some studies have found an increase in the maximal attainable response after stimulation with insulin X10 [18,21], whereas this has not been found by others [11,19,38]. However, it remains a possibility that in some cell types and for some responses, insulin X10 may be able to induce a higher response than human insulin.…”
Section: Understanding Insulin X10mentioning
confidence: 67%
“…It was also noted by these early studies that the binding affinity of insulin X10 to IGF-1R was increased compared with that of human insulin [17,18] but with a fairly low affinity compared with IGF-1 itself, an effect that has subsequently been confirmed by a number of authors [19][20][21][22]. In addition to the increased receptor affinities, [12] insulin X10 was shown to have an increased in vitro ability to stimulate cell growth and DNA synthesis, and Bornfeldt and colleagues speculated that this was due to a substitution in the insulin X10 molecule that made this analogue more chemically similar to the IGF-1 molecule [18]. Compared with human insulin, insulin X10 had an identical 'on-rate' but a much slower 'off-rate' from the IR so that, upon binding, insulin X10 remained bound for much longer than human insulin [17].…”
Section: Understanding Insulin X10mentioning
confidence: 95%
“…Under these conditions the affinity of a certain insulin analogue towards IGF-1R becomes increasingly important. It has been shown that AspB10 and glargine have a six to eightfold and insulin lispro a 1.5-fold higher affinity for IGF-1R than normal insulin [21], while aspart [31] and glulisine [32,33] have a low affinity for IGF-1R, like normal insulin.…”
Section: Discussionmentioning
confidence: 99%
“…V-SEA associated PI3K kinase assay was performed as described previously (Whitman et al, 1985;End et al, 1993;Bornfeldt et al, 1991) with slight modi®cation. Brie¯y, COS-1 cells transfected with wild-type V-SEA (WT-V-SEA) or the various mutants were lysed in HEPES lysis bu er containing 25 mM HEPES, pH 7.5, 150 mM sodium pyrophosphate, 50 mM NaF, 5 mM EDTA, 50 mM b-glycerophosphate, 10% glycerol, 1% Triton-X-100, and protease inhibitor cocktail (Roche).…”
Section: Pi3k Immunocomplex Kinase Assaymentioning
confidence: 99%